Terapi Fibrinolitik Pada Pasien St-Segment Elevation Myocardial Infarction (Stemi) : Review Artikel - Novrianti, Irma; ., Heriani; F, Mustamin (Jurnal Farmasi Udayana, 2021)
Acute ST-elevation myocardial infarction (STEMI) occurs when there is a blockage caused by sudden atherosclerotic plaque that blocks blood flow to the heart. The goal of STEMI therapy is to restore myocardial blood flow, to save the heart. Coronary arterial reproduction recommended by the American Heart Association (AHA) and the Indonesian Cardiovascular Specialist Association (PERKI) is primary percutaneous coronary intervention (PCI) or fibrinolytic. However, not all hospitals have catheterization laboratory facilities, so they still use fibrinolytic as reperfusion therapy. To provide a review of currently available fibrinolytic therapies that can be used in STEMI patients. Four databases [Pubmed, Libgen, researchgate, and Scopus] were searched from 1987 to 2019. Include original articles including RCT, comparative, literature review, and observational study about fibrinolytics treatment in Acute STEMI. Fibrinolytic was divided into specific fibrin (alteplase, tenecteplase, and reteplase) and non-specific fibrin (streptokinase and urokinase). Fibrinolytic used in STEMI are streptokinase, alteplase, tenecteplase, and reteplase. Fibrinolytic can be given when the patient has no contraindications. Furthermore, the administration must follow protocols to minimize the risk of side effects such as bleeding. Fibrinolytic can be used as reperfusion therapy in STEMI patients when PCI cannot be done promptly.